(untitled) (Revista Iberoamericana de Bioética, 2021)
Posthumanism is a term that encompasses numerous theoretical analyses with a common denominator: human exceptionalism, or the privileged position of human beings with regard to the rest of the universe. The purpose of this article is to analyse the extent to which the non-naturalistic structure of the human being has blurred the traditional distinction between what is human and not human, and at the same time, to present a brief overview of the existing debate within posthumanism. Its aim is to question the multiple ways in which posthumanism, in its various configurations, is anti-exceptionalist and challenges our notion of what is “human”.